1975
DOI: 10.2136/sssaj1975.03615995003900050024x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on Denitrification Rate in Soils

Abstract: The effect of temperature on denitrification rate was studied with nine soils differing widely in organic matter content and chemical and physical characteristics. In the range of 15 to 35C, the temperature coefficient of denitrification, Q10, was approximately 2. Denitrification rates at 35 and 45C were similar. Between 10 and 5C, denitrification rate declined abruptly. The lower limit of the temperature range conforming to a Q10 of 2 was estimated to be 11C. In this study of water‐logged soils sealed from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
72
1
2

Year Published

1988
1988
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(84 citation statements)
references
References 0 publications
9
72
1
2
Order By: Relevance
“…The strong non-linear effect of temperature on in stream production of N 2 O (Fig. 7) likely reflects the first order control of microbial activity by temperature that has been well demonstrated for denitrification through laboratory studies (Nowicki 1994;Pfenning and McMahon 1997;Stanford et al 1975). Another field based study of in-stream denitrification also observed a positive relationship between temperature and instream denitrification .…”
Section: Controls Of N 2 and N 2 O Productionmentioning
confidence: 63%
“…The strong non-linear effect of temperature on in stream production of N 2 O (Fig. 7) likely reflects the first order control of microbial activity by temperature that has been well demonstrated for denitrification through laboratory studies (Nowicki 1994;Pfenning and McMahon 1997;Stanford et al 1975). Another field based study of in-stream denitrification also observed a positive relationship between temperature and instream denitrification .…”
Section: Controls Of N 2 and N 2 O Productionmentioning
confidence: 63%
“…(Cassman and Munns 1980;Vigil et al 2002). The negative relationship between T 2 and NNP possibly reflects increased denitrification rates at higher temperatures (Stanford et al 1975). Using the study's (Amundson et al 2003).…”
Section: Precipitation Contextmentioning
confidence: 99%
“…Net nitrate production model R statistical software (The R Foundation for Statistical Computing, Vienna, Austria, 2013) was used to estimate a linear regression specification of NNP at the subfield level, which characterizes a more practical model for assessing and making insights about farmlevel management decisions than NNP at specific 0.6 m 2 sampling locations. Existing literature describes a number of variables that influence N mineralization and denitrification rates; those cited most often include soil temperature (Stanford et al 1973(Stanford et al , 1975Curtin et al 2012), soil water content (Paul et al 2003;Heumann et al 2011) and soil TN (Vigil et al 2002). Other variables discussed in the literature include crop residue C:N ratio (Booth et al 2005;Patron et al 2007), soil organic matter (Booth et al 2005;Heumann et al 2014) and previous crop (Soon and Arshad 2002).…”
Section: N Mineralization and Denitrificationmentioning
confidence: 99%
“…An anaerobic environment with the absence of oxygen gas can help produce more N 2 than some intermediates such as N 2 O (Saleh-Lakha et al, 2009). A temperature range from 15 to 35 °C is optimal for denitrification (Stanford et al, 1975). From these studies, we can see that these limiting factors are unlikely to adversely affect the progress of denitrification in subsurface environments below the ground water table.…”
Section: Soil Desaturation Through the Microbial Denitrificationmentioning
confidence: 88%